Existence of Viscosity Solutions of Second Order Fully Nonlinear Elliptic Equations (Journal of Partial Differential Equations, 1991)
We consider the problem of existence for viscosity solutions of seoond order fully nonlinear elliptic partial differential equations F(D&sup2u, Du, u, z) = 0. We prove existence results for viscosity solutions in W^{1,&#8734} under assumptions that function F satisfies the natural structure conditions. We do not assume F is convex.
Keywords: Viscosity solutions; Second order fully nonlinear elliptic equations; Existence